A Liberal Reading of the Athenian Freedom: Benjamin Constant, Reader of Plutarch’s Solon (De Rebus Antiquis, 2021)
Taking as starting point the appreciation of Constant about the Athenian freedom like herald of  modern liberal spirit, the following article makes a series of statements in relation to more specific ways of understanding that appreciation. In this sense, a key figure analyzed here is Solon of Athens (630 – c.”‰560 BC), to whom Constant arrived through Plutarch. The complete argument of the article is set in the Introduction.
Keywords: Benjamin Constant; Solon of Athens; Plutarch; Political Liberalism